Kajian Mengenai Karakteristik dan Perhitungan Biaya Kecelakaan Lalu Lintas Kota Surabaya - Surahman, Ganda; Springfield, Dzackirendy; Sepriyanna, Irma; Handayasari, Indah (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2025)
Traffic accidents are one of the major issues in urban transportation systems. The occurrence of accidents causes significant losses, both material and immaterial, as well as casualties. This study aims to analyze the characteristics of traffic accidents and calculate accident costs in Surabaya using the Gross Output (Human Capital) Method. Traffic accident data were collected from 2018 to 2023, with victim categories including fatalities, serious injuries, and minor injuries. The study results show that the number of accidents significantly increased in 2022, with the highest percentage rise of 35.52%. The most common type of accident was a front-side collision, while the least frequent accident type was an animal collision. The highest accident occurrence was recorded between 06:00 and 12:00, whereas the lowest occurred between 00:00 and 06:00. The primary cause of accidents was drivers' non-compliant behavior. The accident cost calculation revealed a total economic loss of IDR 804,579,531,473 over the 2018–2023 period, with 2022 recording the highest accident cost of IDR 175,643,804,977, while 2019 recorded the lowest accident cost of IDR 106,492,842,262.